Desain inovatif alat pemotong ring AMDK gelas plastik: Meningkatkan efisiensi dan keamanan proses daur ulang di sektor informal dengan pendekatan value engineering - Wibowo, Eko Ari; Hidayah, Muhammad Nur Wahyu; Munandar, Galih Mahardika; Ardiyansah, Reza; Rahmawati, Nabila Fitri (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The production of plastic glass AMDK waste continues to increase in Indonesia along with the high consumption of bottled drinking water, creating challenges in an efficient recycling process. This research aims to design and prototype a plastic glass ring cutter using a Value Engineering approach, supported by QFD-based requirement analysis and material selection through the AHP method. The tool is designed to improve cutting efficiency, user comfort, and operational safety. Test results showed that the tool was able to reduce cutting time by 58%, produce more uniform cuts, and significantly lower the risk of injury. Main materials of aluminium and stainless steel were used to ensure durability and portability of the tool, making it an ideal solution for the informal sector. This research makes a real contribution in supporting a safer, more efficient and user-friendly plastic waste recycling process.